USING THE SAFE SYSTEM APPROACH TO KEEP OLDER DRIVERS SAFELY MOBILE - Jim LANGFORD (IATSS Research, 2006)
In 2003, Australian road transport jurisdictions collectively accepted that the greatest road safety gains would be achieved through adopting a Safe System approach, derived from Sweden's Vision Zero and the Netherlands' Sustainable Safety strategies. A key objective of all three approaches is to manage vehicles, the road infrastructure, speeds, road users and the interactions between these components, to ensure that in the event of crashes, crash energies will remain at levels that minimize the probability of death and serious injury. Older drivers pose a particular challenge to the Safe System approach, given particularly their greater physical frailty, their driving patterns and for some at least, their reduced fitness to drive. This paper has analyzed the so-called ‘older driver problem’ and identified a number of key factors underpinning their crash levels, for which countermeasures can be identified and implemented within a Safe System framework. The recommended countermeasures consist of: (1) safer roads, through a series of design improvements particularly governing urban intersections; (2) safer vehicles, through both the promotion of crashworthiness as a critical consideration when purchasing a vehicle and the wide use of developed and developing ITS technologies; (3) safer speeds especially at intersections; and (4) safer road users, through both improved assessment procedures to identify the minority of older drivers with reduced fitness to drive and educational efforts to encourage safer driving habits particularly but not only through self-regulation.